A alteridade em Clarice Lispector - Guedes, Helena Cirelli (2014)
Realizing the theme of the otherness in the fiction writed by Clarice Lispector, this study analyses it in the novel The passion according to G. H. and in the short story “A mensagem” with the support of the existentialist philosophy based on Jean-Paul Sartre, Simone de Beauvoir, Frantz Fanon and Søren Kierkegaard and also in the theorists whose works which would probably be nowadays the development of these reflections about the other, among which was chosen Pierre Bourdieu, Kwame Anthony Appiah and Jacques Derrida.